Prohibitin 2 ameliorates cisplatin-induced acute kidney injury by modulating mitochondrial homeostasis - Zhang, Qi; Shi, Xiaoyu; Yao, Lu; Zhou, Ping; Ding, Wei (Frontiers in Physiology, 2025)
Acute kidney injury (AKI), associated with a major health burden globally, is frequently caused by nephrotoxic agents, specifically cisplatin. Prohibitin (PHB) 2, a highly conserved mitochondrial protein localized at the inner mitochondrial membrane, is key to maintaining mitochondrial respiration, cristae morphogenesis, and regulating cell death. Despite being extensively assessed in chronic kidney disease models, the role of PHB2 in AKI, particularly cisplatin-induced AKI, warrants further exploration. Here, we investigated the protective effects of PHB2 in cisplatin-induced AKI in in vitro and in vivo models. The results demonstrated that cisplatin upregulated PHB2 expression both in vitro and in vivo. Mechanistically, PHB2 deficiency exacerbated cisplatin-induced cell apoptosis and mitochondrial dysfunction, indicated by increased caspase-3 activity and reactive oxygen species (ROS) production, as well as mitochondrial membrane potential loss, in vitro. Our Western blot analysis results further validated PHB2’s involvement in autophagy processes within renal tubular cells. Nevertheless, PHB2 overexpression mitigated these detrimental effects, suggesting the protective role of PHB2 in cisplatin-induced AKI. In vivo, adeno-associated virus–mediated PHB2 overexpression reduced cisplatin-induced renal tubular injury and enhanced mitochondrial ultrastructure, supporting its potential therapeutic benefits. Taken together, our findings underscore the protective role of PHB2 in cisplatin-induced AKI, highlighting its potential as a therapeutic target for mitigating renal injury. Future studies elucidating the mechanisms underlying the protective effects of PHB2 and exploring its clinical implications in AKI management are warranted.